KONSEP “MANUSIA EKONOMI” DALAM PEMBANGUNAN EKONOMI DAN PENDIDIKAN - Riswan Jaenudin (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
The essence of economic problems is the use of scarce resources to satisfy unlimitedhuman needs. Scarcity is inevitable and scarcity is central to economic problems. The infinitehuman need is supposedly derived from the philosophy of